Estimation of global solar radiation (gsr) over Biratnagar, Morang, Nepal - Sigdel, Roshan; Pantha, Nurapati (Butwal Campus Journal, 2024)
Solar energy is a renewable source of energy that can be accessed in any geographical place where electricity and other renewable energy sources are inaccessible. In our country, more than half of people still depend on wood, coal, and petroleum for energy, which causes health issues and destroys the environment. Analytical and accurate data related to global solar radiation is essential for harvesting solar energy, which can play an important role in reducing the use of other nonrenewable energy sources. In this study, we calculated Global Solar Radiation (GSR) using the Angstrom-Prescott model, compared it with the measured value using a CMP6 pyranometer, and showed the relation of GSR with some meteorological parameters. The maximum value of GSR was observed on , and the minimum value was on . We have seen a positive correlation of GSR with sunshine duration and air temperature but a negative correlation with relative humidity, rainfall, and atmospheric pressure. Maximum GSR is found in spring and minimum in winter due to fog, minimum sunshine duration, and high maximum relative humidity. Empirical constants and were obtained using Tiwari and Sangeeta models. The accuracy and performance of the applied Angstrom-Prescot model are tested using statistical tools like , , , , , and .